ANALISIS PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN LOLOFITU MOI - Zai, Lucky Fiktori; Ndraha, Ayler Beniah; Mendrofa, Syah Abadi; Lahagu, Palindungan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aimed to understand the utilization of information technology on employee performance at the Lolofitu Moi Sub-District Office. It was found that despite most employees having defined job descriptions, some of them were unable to harness information technology due to limited understanding and skills in technology, as well as issues of accessibility and inadequate infrastructure, particularly concerning stable internet availability. This condition obstructed access and the utilization of information technology, subsequently impacting employee performance. Employing a qualitative method, in-depth interviews were conducted with employees at the Lolofitu Moi Sub-District Office to comprehend their perspectives and experiences regarding the use of information technology and its effects on their performance. The research results revealed that employees faced challenges related to hardware maintenance, software usage, network management, data security, and inadequate infrastructure. Additionally, obstacles in achieving optimal work results, such as differing priorities and expectations between staff and management, and a lack of coordination in task completion were identified. In the context of the office's operations, employee initiatives and mental agility influenced efficiency, while issues of time discipline and attendance were also a primary concern. This research provides a comprehensive overview of the challenges and barriers encountered in utilizing information technology, offering a foundation for further deliberation on improving performance and effectiveness at the Lolofitu Moi Sub-District Office.